(E)-N′-(3,5-Dibromo-2-hydroxybenzylidene)-4-hydroxybenzohydrazide monohydrate - Tao Yang; Guo-Biao Cao; Xiao-Ya Wang (Acta Crystallographica Section E, 2008)
The title compound, C14H10Br2N2O3·H2O, was synthesized by the reaction of 3,5-dibromo-2-hydroxybenzaldehyde with an equimolar amount of 4-hydroxybenzohydrazide in methanol. The structure comprises a Schiff base unit and a water molecule of crystallization. The dihedral angle between the benzene rings in the Schiff base is 1.3 (3)°. In the crystal structure, molecules are linked through intermolecular O—H...O and N—H...O hydrogen bonds, with the water molecule serving as both donor and acceptor. As a result, layers are formed, which are approximately parallel to the bc plane.